Identifying the Weak Foundation of Public Health Resilience forNational Disaster Policy in Indonesia’s Mid-term DevelopmentAgenda 2015–2019: A Policy Content Analysis - Warsito, Gita Miranda; Budiharsana, Meiwita; Burns, Sharyn (UI Scholars Hub, 2020)
Indonesia is one of the most susceptible nations toward natural disasters in the world. Since 1992, approximately 37 tsunami incidents have occurred inIndonesia, with at least 1,244 cases of natural disasters during 2018. Despite the overwhelming impact of disasters on Indonesia, Public Health Resilience,as an approach to disaster countermeasures, has been poorly elaborated in Indonesia’s development agenda (National Mid-term Development Plan (NMDP),or Rencana Pembangunan Jangka Menengah Nasional (RPJMN), 2015 - 2019). By utilizing the method of policy content analysis, this study aimed to analyzethe policy background of Public Health Resilience against disasters in the NMDP 2015 - 2019 and National Disaster Management Authority (NDMA)’s, orBadan Nasional Penanggulangan Bencana (BNPB),Strategic Plan 2015 - 2019. The results showed that the NMDP 2015 - 2019 and NDMA‘s Strategic Plan2015 - 2019 lack the scientific background for Public Health Resilience building in Indonesia. Enhancing the scientific background in these plans will enhancefocus on evidence-based Public Health Resilience establishment.